Adsorptive removal properties of bivalent cadmium from aqueous solution using porous poly(N-2-methyl-4-nitrophenyl maleimide-maleic anhydride-methyl methacrylate) terpolymers. Issue 6 (December 2020) - Dinari, Mohammad; Atabaki, Fariborz; Pahnavar, Zohreh; Soltani, Roozbeh
Graphical abstract: Highlights: Terpolymers material were easily prepared using commercially accessible monomers. Synthesized Terpolymers were used as on adsorbent for Cd(II) removal from water. Different non-linear isotherm and kinetic models were applied for the interpretation of experimental data. The Langmuir maximum adsorption capacity of Terpolymer 1 toward Cd(II) was found to be 77.56 mg g −1 . These Terpolymers have good potential for uptake of Cd(II) from aqueous solutions. Abstract: Our world is in the midst of a clean water crisis and freshwater scarcity. It is no longer news that heavy metals, particularly cadmium species, are environmental toxic pollutants threatening the health of both humans and the animals. Cadmium is discharged into the aqueous environment by various natural processes such as sedimentary rocks, weathering and erosion of rock, earth's crust, marine phosphate and phosphorites, forest fires, etc . In this regard, attempts at heavy metals remediation from contaminated water are attracting considerable interest worldwide. The adsorption is a facile process to encounter heavy metal pollution. Accordingly, for the first time, a composite polymeric material ( N -2-methyl-4 nitrophenyl maleimide-maleic anhydride-methyl methacrylate) terpolymer has been applied for adsorption of bivalent cadmium from aqueous solution. Three types of monomeric components, including N -2-methyl-4-nitrophenyl maleimide, maleic anhydride, and methyl methacrylate, which are economically accessible monomers, were used for the synthesis of three terpolymers with various mole compositions. Maximum Cd(II) removal by terpolymers was observed at pH 7.0. Terpolymer 1 was chosen for further adsorption investigation. Four types of non-linear forms of kinetic and isotherm equations were used for the interpretation of obtained experimental data. The calculated Langmuir maximum uptake of Cd(II) was found to be 77.56 mg g −1 . Furthermore, the adsorbents can easily separate from the water with lower total cost and energy after adsorption compared to powder-type adsorbents. Hence, we conclude that this terpolymer could be utilized as an effective and economically adsorbent for the removal of bivalent cadmium from water by adsorption method.